High-strength wear-resistant cemented carbide tool bit material and preparation method thereof

CN122959640APending Publication Date: 2026-10-23ZHEJIANG FANGDA TUNGSTEN CARBIDE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611373957.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]本发明提供了一种高强耐磨硬质合金刀头材料及其制备方法,解决了传统硬质合金刀头材料晶粒组织可控性差,硬度、耐磨性不佳,导致在高摩擦、强冲击工况下磨损速度快、使用寿命短,且刀头切削区域温度急剧升高,导致刀头切削精度快速衰减,加工稳定性大幅降低的问题

Benefits of technology

(1)本发明技术方案中,在碳纤维表面合成致密的多孔碳层,一方面,碳纤维能够在硬质合金刀头材料内部形成交错纤维网络,桥接晶界裂纹,抑制冲击载荷下裂纹快速扩展,且碳纤维具有较高的耐磨性能,进而能够提升硬质合金刀头材料的机械强度和耐磨性能,另一方面,多孔碳层在碳纤维表面形成自润滑效应,降低刀头材料与岩层之间的磨损,提高硬质合金刀头材料的耐磨性能,且多孔碳层作为柔性过渡缓冲层,能够分散碳纤维与基体因热膨胀系数差异产生的热应力,避免高温冲击载荷下界面微裂纹的产生,影响硬质合金刀头材料的耐磨性能和机械性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application relates to the technical field of alloy tool bits, and discloses a high-strength wear-resistant hard alloy tool bit material and a preparation method thereof, which comprises the following raw materials in parts by mass: tungsten carbide powder 90-100 parts, cobalt powder 13-15 parts, nickel powder 3-5 parts, molybdenum powder 2-3 parts and additives 2-3 parts. The hard alloy tool bit material prepared by taking tungsten carbide as a matrix and adding cobalt powder, nickel powder, molybdenum powder and additives has high mechanical strength, wear resistance and high-temperature resistance; and the hard alloy tool bit material has good grain structure and has high service life under high friction and strong impact working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy cutting tool technology, specifically to a high-strength, wear-resistant cemented carbide cutting tool material and its preparation method. Background Technology

[0002] Hard alloy is an alloy material made by powder metallurgy of hard carbides of refractory metals and binder metals. Due to its high hardness, wear resistance, good strength and toughness, heat resistance and corrosion resistance, especially its high strength and wear resistance, hard alloy is widely used in industries such as construction engineering, mining and oil drilling, machining and aerospace.

[0003] Carbide cutting tools are high-precision cutting and rock drilling tools made from a carbide matrix. They mainly use tungsten carbide and titanium carbide as hard reinforcing phases and cobalt metal as the binder phase. The high-hardness and high-rigidity alloy substrate is obtained through powder metallurgy sintering. The hardness, heat resistance and impact toughness of the material can be adjusted according to the composition ratio, making them widely suitable for various high-intensity and high-load processing scenarios. At present, these cutting tools are widely used in oilfield drilling tools, mining rock drilling equipment, coal mining equipment and other engineering instruments to complete efficient processing under harsh conditions such as uneven surfaces and intermittent cutting.

[0004] With the improvement of the overall technical level of the new hard material products industry, especially the improvement of the competitiveness of high-end products, there are increasingly higher requirements for the mechanical properties of cutting tools. Traditional cemented carbide cutting materials have poor controllability of grain structure, poor hardness and wear resistance, resulting in fast wear and short service life under high friction and strong impact conditions. In addition, the temperature of the cutting area of ​​the cutting head rises sharply, resulting in rapid decay of cutting accuracy and a significant reduction in processing stability.

[0005] Therefore, it is necessary to research a wear-resistant, high-temperature resistant, and high-strength cemented carbide cutting tool material. Summary of the Invention

[0006] This invention provides a high-strength, wear-resistant cemented carbide cutting tool material and its preparation method, which solves the problems of poor controllability of grain structure, poor hardness and wear resistance of traditional cemented carbide cutting tool materials, resulting in fast wear rate and short service life under high friction and strong impact conditions, and the sharp increase in temperature in the cutting area of ​​the cutting tool, which leads to rapid decay of cutting accuracy and a significant reduction in machining stability.

[0007] The technical solution of this invention: A high-strength, wear-resistant cemented carbide cutting tool material comprises the following raw materials in parts by weight: 90-100 parts tungsten carbide powder, 13-15 parts cobalt powder, 3-5 parts nickel powder, 2-3 parts molybdenum powder, and 2-3 parts additives. The additive is obtained by reacting composite carbon fibers with tetrabutyl titanate. The composite carbon fiber is obtained by synthesizing a porous carbon layer on the surface of pretreated carbon fiber, and then mixing and reacting it with carboxymethyl cellulose, zirconium powder, tantalum powder and molybdenum powder.

[0008] A method for preparing a high-strength, wear-resistant cemented carbide cutting tip material includes the following preparation steps: S1. Tungsten carbide, cobalt powder, nickel powder, molybdenum powder, and additives are mixed, vacuum dried, and ball-milled to obtain a mixture; S2. The mixture is placed in a pressure mold to be pressed into a preform, and then the preform is placed in a sintering furnace for sintering and solid solution strengthening. After cooling to room temperature, it is ground and sharpened to obtain cemented carbide cutting tool material. Further, in step S1, the vacuum drying specifically involves a drying temperature of 70-90℃, a vacuum degree of 4-6Pa, and a drying time of 1-2 hours.

[0009] Further, in step S1, the ball milling is carried out using a ball mill, the ball material is tungsten-cobalt alloy balls with a diameter of 10 mm, the ball-to-material ratio is (15-20):1, the rotation speed is 200-300 r / min, and the ball milling time is 20-24 h.

[0010] Furthermore, in step S2, the pressing pressure is 200-300 MPa, and the pressing time is 1-2 min.

[0011] Further, in step S2, the sintering specifically involves heating to 1200-1400℃ at a rate of 2-5℃ / min and sintering for 2-3 hours.

[0012] Furthermore, the additive is specifically prepared by the following steps: A1. Mix glucose, potassium hydroxide and deionized water, stir well to form a mixture, impregnate carbon fiber in the mixture, remove it after impregnation, dry it until the water evaporates, place it in a tube furnace, introduce nitrogen gas, carbonize at 750-850℃ for 3-4 hours, remove it, cool it to room temperature, wash it, dry it to obtain modified carbon fiber. A2. Mix zirconium powder, tantalum powder, molybdenum powder and carboxymethyl cellulose aqueous solution, stir evenly, then add modified carbon fiber, stir at 80-120 r / min for 20-30 min, let stand, filter, wash, and dry until the water evaporates to obtain composite carbon fiber; A3. Add tetrabutyl titanate to ethanol and deionized water, stir at 40-50℃ for 1-2 hours, cool to room temperature, add hydrochloric acid to adjust the pH to 2-3, and continue stirring to obtain titanium dioxide sol; mix titanium dioxide sol with composite carbon fiber and stir evenly to obtain additive.

[0013] Furthermore, in the A1 reaction process described above, the carbon fiber is formed after degumming, heat treatment, and sodium hydroxide treatment. It has high activity and surface roughness, which is beneficial for synthesizing a dense porous carbon layer on the surface of the carbon fiber. Carbon fiber has high activity and surface roughness. A mixture of glucose and potassium hydroxide solution is formed. Carbon fiber is impregnated into the mixture, which allows glucose and potassium hydroxide activator to be adsorbed on the surface of the carbon fiber. After sintering and carbonization, glucose is decomposed by heat to form a dense carbon layer. Potassium hydroxide, as an activator, can form channels on the surface of the dense carbon layer, thereby achieving the synthesis of a porous carbon layer on the surface of carbon fiber and obtaining modified carbon fiber.

[0014] Furthermore, during the A2 reaction process described above, the modified carbon fiber is impregnated in an aqueous solution of carboxymethyl cellulose. The aqueous solution of carboxymethyl cellulose has high adhesive properties, which allows the carboxymethyl cellulose to adhere to the surface of the modified carbon fiber and the pores of the porous carbon layer on the surface. Furthermore, the adhesive properties of carboxymethyl cellulose allow zirconium powder, tantalum powder, and molybdenum powder to adhere to the surface of the modified carbon fiber, forming a metal layer of zirconium powder, tantalum powder, and molybdenum powder on the surface of the modified carbon fiber, thus obtaining composite carbon fiber.

[0015] Furthermore, during the A3 reaction process described above, the composite carbon fiber and titanium dioxide sol are mixed, so that the titanium dioxide sol is uniformly coated on the surface of the composite carbon fiber, thus obtaining an additive.

[0016] Further, in step A1, the mass ratio of glucose, potassium hydroxide and deionized water is (5.5-5.8):(4-4.5):100.

[0017] Further, in step A1, the mass ratio of the carbon fiber to the mixture is (20-25):100.

[0018] Further, in step A2, the mass ratio of zirconium powder, tantalum powder, molybdenum powder, carboxymethyl cellulose aqueous solution and modified carbon fiber is 1:1:1:(90-120):(5-5.5).

[0019] Further, in step A3, the mass ratio of tetrabutyl titanate, ethanol and deionized water is (13-17):(30-40):(8-12).

[0020] Further, in step A3, the mass ratio of the titanium dioxide sol to the composite carbon fiber is (0.2-0.4):1.

[0021] The present invention has the following beneficial effects: (1) In the technical solution of the present invention, a dense porous carbon layer is synthesized on the surface of carbon fiber. On the one hand, carbon fiber can form an interlaced fiber network inside the cemented carbide cutting tool material, bridge grain boundary cracks, and inhibit the rapid propagation of cracks under impact load. In addition, carbon fiber has high wear resistance, which can improve the mechanical strength and wear resistance of cemented carbide cutting tool material. On the other hand, the porous carbon layer forms a self-lubricating effect on the surface of carbon fiber, reduces the wear between the cutting tool material and the rock layer, and improves the wear resistance of cemented carbide cutting tool material. In addition, the porous carbon layer, as a flexible transition buffer layer, can disperse the thermal stress generated by the difference in thermal expansion coefficient between carbon fiber and matrix, avoid the generation of interface microcracks under high temperature impact load, and affect the wear resistance and mechanical properties of cemented carbide cutting tool material.

[0022] (2) In the technical solution of the present invention, zirconium powder, tantalum powder and molybdenum powder are adhered to the surface of modified carbon fiber through carboxymethyl cellulose, and the porous carbon contained on the surface of modified carbon fiber has high adsorption performance, serving as a carrier for zirconium powder, tantalum powder and molybdenum powder, so that zirconium powder, tantalum powder and molybdenum powder are dispersed at the grain boundaries of cemented carbide cutting head material through modified carbon fiber. During the sintering process, carboxymethyl cellulose is decomposed by heat to form carbon elements, and the formed carbon elements can form zirconium carbide, tantalum carbide and molybdenum carbide with zirconium powder, tantalum powder and molybdenum powder, which fill the grain boundaries of cemented carbide cutting head material, improve the density of cemented carbide cutting head material, and thus improve the mechanical strength, wear resistance and high temperature resistance of cemented carbide cutting head material; Zirconium carbide delays crack propagation through crack deflection and bridging mechanisms; tantalum carbide promotes crack bifurcation, grain boundary slip, and refines the grain size of cemented carbide cutting tool materials; molybdenum carbide inhibits grain growth in cemented carbide cutting tool materials, thereby improving the performance of cemented carbide materials; through the interaction of zirconium carbide, tantalum carbide, and molybdenum carbide, the mechanical strength, wear resistance, and high-temperature resistance of cemented carbide cutting tool materials are improved.

[0023] (3) In the technical solution of the present invention, titanium dioxide sol is uniformly coated on the surface of composite carbon fiber. On the one hand, during the sintering process, titanium dioxide in titanium dioxide sol can react with tungsten carbide to generate titanium carbide with high hardness. They are dispersed in the matrix and can jointly bear the external load, improve the mechanical strength, wear resistance and high temperature resistance of cemented carbide cutting head material. On the other hand, the carbon element provided by carboxymethyl cellulose in composite carbon fiber can also participate in the reaction of titanium dioxide to form titanium carbide. The formed titanium carbide is coated on the surface of composite carbon fiber, thereby fixing the metal carbide formed by composite carbon fiber during the sintering process, avoiding the metal carbide from slipping under high temperature impact load, which affects the mechanical strength, wear resistance and high temperature resistance of cemented carbide cutting head material.

[0024] (4) In the technical solution of the present invention, the cemented carbide cutting tool material prepared by adding cobalt powder, nickel powder, molybdenum powder and additives as tungsten carbide matrix has high mechanical strength, wear resistance and high temperature resistance; and the cemented carbide cutting tool material has good grain structure and has a long service life under high friction and strong impact conditions. Detailed Implementation

[0025] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0026] The raw materials used in the embodiments of this invention are shown below, and all reagents used are analytical grade.

[0027] The tungsten carbide powder has a particle size of 1-3μm and was purchased from Hebei Yuechao Wear-resistant Materials Co., Ltd.

[0028] The cobalt powder has a particle size of 1μm, the nickel powder has a particle size of 1μm, the molybdenum powder has a particle size of 1μm, the tantalum powder has a particle size of 100nm, and the zirconium powder (item number ST-M-015-1) has a particle size of 1μm. These powders were purchased from Shanghai Shuitian Materials Technology Co., Ltd.

[0029] The carboxymethyl cellulose, product number C804618, MW700000 (DS=0.9), 2500-4500 mPa.s, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0030] The tungsten-cobalt alloy balls were purchased from Dongguan Jinhong Steel Ball Co., Ltd.

[0031] The carbon fiber is a nanofiber with a diameter of 200 nm and a length of 10 μm, purchased from Zhongke Jinyan (Beijing) Technology Co., Ltd.

[0032] Carbon fiber is formed through degumming, heat treatment, and sodium hydroxide treatment. The specific steps are as follows: Carbon fibers were placed in a sintering furnace and heated to 400°C for 120 minutes to burn off the surface organic binder. They were then soaked in acetone solution for 60 minutes to dissolve the coke. After washing with deionized water and drying, degummed carbon fibers were obtained. The degummed carbon fiber bundles were placed in a 1 mol / L sodium hydroxide solution for roughening treatment, while being rotated and heated on a smart magnetic stirrer for 15 minutes. The carbon fibers were then removed, rinsed with deionized water until neutral, and then placed in a constant temperature drying oven for heating and drying to increase the surface roughness and polar groups of the fibers, thereby improving surface activity and affinity with the metal matrix, preparing for the metallization of the carbon fiber surface.

[0033] Example 1 A high-strength, wear-resistant cemented carbide cutting tool material comprises the following raw materials in parts by weight: 90 parts tungsten carbide powder, 13 parts cobalt powder, 3 parts nickel powder, 2 parts molybdenum powder, and 2 parts additives; A method for preparing a high-strength, wear-resistant cemented carbide cutting tip material includes the following preparation steps: S1. Mix tungsten carbide, cobalt powder, nickel powder, molybdenum powder, and additives, and vacuum dry at 70-90℃ and 4Pa for 1 hour. Then ball mill the mixture to obtain the mixture. The ball milling is carried out using a ball mill, with tungsten-cobalt alloy balls with a diameter of 10mm, a ball-to-material ratio of 15:1, a rotation speed of 200r / min, and a ball milling time of 20 hours. S2. Place the mixture in a pressure mold and press it at 200MPa for 1 minute to form a preform. Then place the preform in a sintering furnace for sintering and solution strengthening. Cool to room temperature, grind and sharpen to obtain cemented carbide cutting tool material. The sintering process is as follows: heat to 1200℃ at a rate of 2℃ / min and sinter for 2 hours.

[0034] The additive is prepared by the following steps: A1. Glucose, potassium hydroxide, and deionized water were mixed in a mass ratio of 5.5:4:100 and stirred until homogeneous to form a mixture. Carbon fibers were then impregnated in the mixture. After impregnation, the carbon fibers were removed and dried in an oven at 100°C until the moisture evaporated. The mixture was then placed in a tube furnace, nitrogen gas was introduced, and carbonization was carried out at 750°C for 3 hours. The carbon fibers were then removed, cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C for 40 minutes to obtain modified carbon fibers. The mass ratio of carbon fibers to the mixture was 20:100. A2. Zirconium powder, tantalum powder, molybdenum powder, and a 2% (w / w) carboxymethyl cellulose aqueous solution are mixed and stirred evenly. Modified carbon fiber is then added, and the mixture is stirred at 80 r / min for 20 min, allowed to stand for 30 min, filtered, washed three times with deionized water, and dried in a 90℃ oven until the moisture evaporates to obtain composite carbon fiber. The mass ratio of zirconium powder, tantalum powder, molybdenum powder, carboxymethyl cellulose aqueous solution, and modified carbon fiber is 1:1:1:90:5. A3. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 40°C for 1 hour, cooled to room temperature, and the pH was adjusted to 2 with 0.5 mol / L hydrochloric acid. Stirring was continued for 24 hours to obtain titanium dioxide sol. The titanium dioxide sol and composite carbon fiber were mixed and stirred evenly to obtain the additive. The mass ratio of tetrabutyl titanate, ethanol and deionized water was 13:30:8; the mass ratio of titanium dioxide sol and composite carbon fiber was 0.2:1.

[0035] Example 2 A high-strength, wear-resistant cemented carbide cutting tool material comprises the following raw materials in parts by weight: 95 parts tungsten carbide powder, 14 parts cobalt powder, 4 parts nickel powder, 2.5 parts molybdenum powder, and 2.5 parts additives; A method for preparing a high-strength, wear-resistant cemented carbide cutting tip material includes the following preparation steps: S1. Tungsten carbide, cobalt powder, nickel powder, molybdenum powder, and additives are mixed and vacuum dried at 80℃ and 5Pa for 1.5h. The mixture is then ball-milled to obtain the mixture. The ball milling is performed using a ball mill, with tungsten-cobalt alloy balls of 10mm in diameter. The ball-to-material ratio is 18:1, the rotation speed is 250r / min, and the ball milling time is 22h. S2. Place the mixture in a pressure mold and press it at 250MPa for 1.5min to form a preform. Then place the preform in a sintering furnace for sintering and solution strengthening. Cool to room temperature, grind and sharpen to obtain cemented carbide cutting tool material. The sintering process is as follows: heat to 1300℃ at a rate of 3℃ / min and sinter for 2.5h.

[0036] The additive is prepared by the following steps: A1. Glucose, potassium hydroxide, and deionized water were mixed in a mass ratio of 5.7:4.3:100 and stirred until homogeneous to form a mixture. Carbon fibers were then impregnated in the mixture. After impregnation, the carbon fibers were removed and dried in an oven at 100°C until the moisture evaporated. The mixture was then placed in a tube furnace, nitrogen gas was introduced, and carbonization was carried out at 800°C for 3.5 hours. The carbon fibers were then removed, cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C for 40 minutes to obtain modified carbon fibers. The mass ratio of carbon fibers to the mixture was 23:100. A2. Zirconium powder, tantalum powder, molybdenum powder, and a 2% (w / w) carboxymethyl cellulose aqueous solution are mixed and stirred evenly. Modified carbon fiber is then added, and the mixture is stirred at 100 r / min for 25 min. After standing for 30 min, the mixture is filtered, washed three times with deionized water, and dried in a 90℃ oven until the moisture evaporates to obtain composite carbon fiber. The mass ratio of zirconium powder, tantalum powder, molybdenum powder, carboxymethyl cellulose aqueous solution, and modified carbon fiber is 1:1:1:100:5.3. A3. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 45°C for 1.5 h, cooled to room temperature, and the pH was adjusted to 2.5 with 0.5 mol / L hydrochloric acid. Stirring was continued for 24 h to obtain titanium dioxide sol. The titanium dioxide sol and composite carbon fiber were mixed and stirred evenly to obtain the additive. The mass ratio of tetrabutyl titanate, ethanol and deionized water was 15:35:10; the mass ratio of titanium dioxide sol and composite carbon fiber was 0.3:1.

[0037] Example 3 A high-strength, wear-resistant cemented carbide cutting tool material comprises the following raw materials in parts by weight: 100 parts tungsten carbide powder, 15 parts cobalt powder, 5 parts nickel powder, 3 parts molybdenum powder, and 3 parts additives. A method for preparing a high-strength, wear-resistant cemented carbide cutting tip material includes the following preparation steps: S1. Mix tungsten carbide, cobalt powder, nickel powder, molybdenum powder, and additives, and vacuum dry at 90℃ and 6Pa for 2 hours. Then ball mill the mixture to obtain the mixture. The ball milling is carried out using a ball mill, and the ball material is tungsten-cobalt alloy balls with a diameter of 10mm. The ball-to-material ratio is 20:1, the rotation speed is 300r / min, and the ball milling time is 24 hours. S2. Place the mixture in a pressure mold and press it at 300MPa for 2 minutes to form a preform. Then place the preform in a sintering furnace for sintering and solid solution strengthening. After cooling to room temperature, grind and sharpen to obtain cemented carbide cutting tool material. The sintering process is as follows: heat up to 1400℃ at a rate of 5℃ / min and sinter for 3 hours.

[0038] The additive is prepared by the following steps: A1. Glucose, potassium hydroxide, and deionized water were mixed in a mass ratio of 5.8:4.5:100 and stirred until homogeneous to form a mixture. Carbon fibers were then impregnated in the mixture. After impregnation, the carbon fibers were removed and dried in an oven at 100°C until the moisture evaporated. The mixture was then placed in a tube furnace, nitrogen gas was introduced, and carbonization was carried out at 850°C for 4 hours. The carbon fibers were then removed, cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C for 40 minutes to obtain modified carbon fibers. The mass ratio of carbon fibers to the mixture was 25:100. A2. Zirconium powder, tantalum powder, molybdenum powder, and a 2% (w / w) carboxymethyl cellulose aqueous solution are mixed and stirred evenly. Modified carbon fiber is then added, and the mixture is stirred at 120 r / min for 30 min. After standing for 30 min, the mixture is filtered, washed three times with deionized water, and dried in a 90℃ oven until the moisture evaporates to obtain composite carbon fiber. The mass ratio of zirconium powder, tantalum powder, molybdenum powder, carboxymethyl cellulose aqueous solution, and modified carbon fiber is 1:1:1:120:5.5. A3. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 50°C for 2 hours, cooled to room temperature, and the pH was adjusted to 3 with 0.5 mol / L hydrochloric acid. Stirring was continued for 24 hours to obtain titanium dioxide sol. The titanium dioxide sol and composite carbon fiber were mixed and stirred evenly to obtain the additive. The mass ratio of tetrabutyl titanate, ethanol and deionized water was 17:40:12; the mass ratio of titanium dioxide sol and composite carbon fiber was 0.4:1.

[0039] Comparative Example 1 The only difference between this comparative example and Example 3 is the preparation of the additives, as detailed below: The additive is prepared by the following steps: A1. Zirconium powder, tantalum powder, molybdenum powder, and a 2% (w / w) carboxymethyl cellulose aqueous solution are mixed and stirred evenly. Then, carbon fiber is added, and the mixture is stirred at 120 r / min for 30 min. After standing for 30 min, it is filtered, washed three times with deionized water, and dried in a 90℃ oven until the moisture evaporates to obtain composite carbon fiber. The mass ratio of zirconium powder, tantalum powder, molybdenum powder, carboxymethyl cellulose aqueous solution, and carbon fiber is 1:1:1:120:5.5. A2. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 50°C for 2 hours, cooled to room temperature, and the pH was adjusted to 3 with 0.5 mol / L hydrochloric acid. Stirring was continued for 24 hours to obtain titanium dioxide sol. The titanium dioxide sol and composite carbon fiber were mixed and stirred evenly to obtain the additive. The mass ratio of tetrabutyl titanate, ethanol and deionized water was 17:40:12; the mass ratio of titanium dioxide sol and composite carbon fiber was 0.4:1.

[0040] Comparative Example 2 The only difference between this comparative example and Example 3 is the preparation of the additives, as detailed below: The additive is prepared by the following steps: A1. Glucose, potassium hydroxide, and deionized water were mixed in a mass ratio of 5.8:4.5:100 and stirred until homogeneous to form a mixture. Carbon fibers were then impregnated in the mixture. After impregnation, the carbon fibers were removed and dried in an oven at 100°C until the moisture evaporated. The mixture was then placed in a tube furnace, nitrogen gas was introduced, and carbonization was carried out at 850°C for 4 hours. The carbon fibers were then removed, cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C for 40 minutes to obtain modified carbon fibers. The mass ratio of carbon fibers to the mixture was 25:100. A2. Tantalum powder, molybdenum powder, and a 2% (w / w) carboxymethyl cellulose aqueous solution are mixed and stirred evenly. Modified carbon fiber is then added, and the mixture is stirred at 120 r / min for 30 min. After standing for 30 min, the mixture is filtered, washed three times with deionized water, and dried in a 90℃ oven until the moisture evaporates to obtain composite carbon fiber. The mass ratio of tantalum powder, molybdenum powder, carboxymethyl cellulose aqueous solution, and modified carbon fiber is 1:1:120:6.5. A3. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 50°C for 2 hours, cooled to room temperature, and the pH was adjusted to 3 with 0.5 mol / L hydrochloric acid. Stirring was continued for 24 hours to obtain titanium dioxide sol. The titanium dioxide sol and composite carbon fiber were mixed and stirred evenly to obtain the additive. The mass ratio of tetrabutyl titanate, ethanol and deionized water was 17:40:12; the mass ratio of titanium dioxide sol and composite carbon fiber was 0.4:1.

[0041] Comparative Example 3 The only difference between this comparative example and Example 3 is the preparation of the additives, as detailed below: The additive is prepared by the following steps: A1. Glucose, potassium hydroxide, and deionized water were mixed in a mass ratio of 5.8:4.5:100 and stirred until homogeneous to form a mixture. Carbon fibers were then impregnated in the mixture. After impregnation, the carbon fibers were removed and dried in an oven at 100°C until the moisture evaporated. The mixture was then placed in a tube furnace, nitrogen gas was introduced, and carbonization was carried out at 850°C for 4 hours. The carbon fibers were then removed, cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C for 40 minutes to obtain modified carbon fibers. The mass ratio of carbon fibers to the mixture was 25:100. A2. Zirconium powder, molybdenum powder, and a 2% (w / w) carboxymethyl cellulose aqueous solution are mixed and stirred evenly. Modified carbon fiber is then added, and the mixture is stirred at 120 r / min for 30 min. After standing for 30 min, the mixture is filtered, washed three times with deionized water, and dried in a 90℃ oven until the moisture evaporates to obtain composite carbon fiber. The mass ratio of zirconium powder, molybdenum powder, carboxymethyl cellulose aqueous solution, and modified carbon fiber is 1:1:120:6.5. A3. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 50°C for 2 hours, cooled to room temperature, and the pH was adjusted to 3 with 0.5 mol / L hydrochloric acid. Stirring was continued for 24 hours to obtain titanium dioxide sol. The titanium dioxide sol and composite carbon fiber were mixed and stirred evenly to obtain the additive. The mass ratio of tetrabutyl titanate, ethanol and deionized water was 17:40:12; the mass ratio of titanium dioxide sol and composite carbon fiber was 0.4:1.

[0042] Comparative Example 4 The only difference between this comparative example and Example 3 is the preparation of the additives, as detailed below: The additive is prepared by the following steps: A1. Glucose, potassium hydroxide, and deionized water were mixed in a mass ratio of 5.8:4.5:100 and stirred until homogeneous to form a mixture. Carbon fibers were then impregnated in the mixture. After impregnation, the carbon fibers were removed and dried in an oven at 100°C until the moisture evaporated. The mixture was then placed in a tube furnace, nitrogen gas was introduced, and carbonization was carried out at 850°C for 4 hours. The carbon fibers were then removed, cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C for 40 minutes to obtain modified carbon fibers. The mass ratio of carbon fibers to the mixture was 25:100. A2. Zirconium powder, tantalum powder, and a 2% (w / w) carboxymethyl cellulose aqueous solution were mixed and stirred evenly. Modified carbon fiber was then added, and the mixture was stirred at 120 r / min for 30 min. After standing for 30 min, the mixture was filtered, washed three times with deionized water, and dried in a 90℃ oven until the moisture evaporated to obtain composite carbon fiber. The mass ratio of zirconium powder, tantalum powder, carboxymethyl cellulose aqueous solution, and modified carbon fiber was 1:1:120:6.5. A3. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 50°C for 2 hours, cooled to room temperature, and the pH was adjusted to 3 with 0.5 mol / L hydrochloric acid. Stirring was continued for 24 hours to obtain titanium dioxide sol. The titanium dioxide sol and composite carbon fiber were mixed and stirred evenly to obtain the additive. The mass ratio of tetrabutyl titanate, ethanol and deionized water was 17:40:12; the mass ratio of titanium dioxide sol and composite carbon fiber was 0.4:1.

[0043] Comparative Example 5 The only difference between this comparative example and Example 3 is the preparation of the additives, as detailed below: The additive is prepared by the following steps: A1. Glucose, potassium hydroxide, and deionized water were mixed in a mass ratio of 5.8:4.5:100 and stirred until homogeneous to form a mixture. Carbon fibers were then impregnated in the mixture. After impregnation, the carbon fibers were removed and dried in an oven at 100°C until the moisture evaporated. The mixture was then placed in a tube furnace, nitrogen gas was introduced, and carbonization was carried out at 850°C for 4 hours. The carbon fibers were then removed, cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C for 40 minutes to obtain modified carbon fibers. The mass ratio of carbon fibers to the mixture was 25:100. A2. Mix zirconium powder, tantalum powder, and molybdenum powder, stir evenly, then add modified carbon fiber, stir at 120 r / min for 30 min, and dry in an oven at 90℃ to obtain composite carbon fiber; the mass ratio of zirconium powder, tantalum powder, molybdenum powder, and modified carbon fiber is 1:1:1:5.5. A3. Tetrabutyl titanate was added to ethanol and deionized water, stirred at 50°C for 2 hours, cooled to room temperature, and the pH was adjusted to 3 with 0.5 mol / L hydrochloric acid. Stirring was continued for 24 hours to obtain titanium dioxide sol. The titanium dioxide sol and composite carbon fiber were mixed and stirred evenly to obtain the additive. The mass ratio of tetrabutyl titanate, ethanol and deionized water was 17:40:12; the mass ratio of titanium dioxide sol and composite carbon fiber was 0.4:1.

[0044] Comparative Example 6 The only difference between this comparative example and Example 3 is the preparation of the additives, as detailed below: The additive is prepared by the following steps: A1. Glucose, potassium hydroxide, and deionized water were mixed in a mass ratio of 5.8:4.5:100 and stirred until homogeneous to form a mixture. Carbon fibers were then impregnated in the mixture. After impregnation, the carbon fibers were removed and dried in an oven at 100°C until the moisture evaporated. The mixture was then placed in a tube furnace, nitrogen gas was introduced, and carbonization was carried out at 850°C for 4 hours. The carbon fibers were then removed, cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C for 40 minutes to obtain modified carbon fibers. The mass ratio of carbon fibers to the mixture was 25:100. A2. Mix zirconium powder, tantalum powder, molybdenum powder and a 2% (w / w) carboxymethyl cellulose aqueous solution, stir evenly, then add modified carbon fiber, stir at 120 r / min for 30 min, let stand for 30 min, filter, wash three times with deionized water, and dry in a 90℃ oven until the moisture evaporates to obtain the additive; the mass ratio of zirconium powder, tantalum powder, molybdenum powder, carboxymethyl cellulose aqueous solution and modified carbon fiber is 1:1:1:120:5.5.

[0045] The performance of the cemented carbide tool tip materials prepared in Examples 1-3 and Comparative Examples 1-6 was then tested.

[0046] Wear resistance test: The wear resistance of the prepared cemented carbide tool tip material was tested according to GB / T34501-2017 standard.

[0047] Hardness (HRA) test: The hardness value of the prepared cemented carbide tool tip material was tested according to the standard GB / T3849.1-2015.

[0048] Mechanical property testing: The tensile strength of the prepared cemented carbide cutting tool material was tested according to GB / T228.1-2021 "Metallic materials - Tensile testing - Part 1: Test method at room temperature"; the tensile strength of the cemented carbide cutting tool material at 600℃ was tested according to GB / T228.2-2015 "Metallic materials - Tensile testing - Part 2: Test method at high temperature" to demonstrate the high temperature resistance of the cemented carbide material.

[0049] The test results are shown in Tables 1 and 2 below.

[0050] Table 1. Performance testing of cemented carbide tool tip materials prepared in Examples 1-3 and Comparative Examples 1-6

[0051] Table 2. Performance testing of cemented carbide tool tip materials prepared in Examples 1-3 and Comparative Examples 1-6

[0052] As can be seen from the data in Table 1, the cemented carbide cutting tool materials prepared in Examples 1-3 have high mechanical strength, wear resistance and high temperature resistance; and the cemented carbide cutting tool materials have good grain structure and have a long service life under high friction and strong impact conditions.

[0053] Comparative Example 1 showed that when modified carbon fiber was replaced with additives made from carbon fiber and added to the cemented carbide cutting tool material, its performance decreased. This demonstrates that the porous carbon layer forms a self-lubricating effect on the carbon fiber surface, reducing wear between the cutting tool material and the rock layer, and improving the wear resistance of the cemented carbide cutting tool material. Furthermore, the porous carbon layer, as a flexible transition buffer layer, can disperse the thermal stress generated by the difference in thermal expansion coefficients between the carbon fiber and the matrix, avoiding the generation of interfacial microcracks under high-temperature impact loads, which would affect the wear resistance and mechanical properties of the cemented carbide cutting tool material.

[0054] Additives prepared by replacing zirconium powder (equal mass) with modified carbon fiber in Comparative Example 2, tantalum powder (equal mass) with modified carbon fiber in Comparative Example 3, and molybdenum powder (equal mass) with modified carbon fiber in Comparative Example 4, when added to cemented carbide cutting tool materials, resulted in a decrease in performance. This demonstrates that the carbon elements formed by the thermal decomposition of carboxymethyl cellulose can combine with zirconium powder, tantalum powder, and molybdenum powder to form zirconium carbide, tantalum carbide, and molybdenum carbide, which fill the grain boundaries of the cemented carbide cutting tool material, increasing its density and thus improving its mechanical strength, wear resistance, and high-temperature resistance. Specifically, zirconium carbide delays crack propagation through crack deflection and bridging mechanisms; tantalum carbide promotes crack bifurcation, grain boundary slip, and refines the grains of the cemented carbide cutting tool material; and molybdenum carbide inhibits grain growth, improving the material's performance. Through the interaction of zirconium carbide, tantalum carbide, and molybdenum carbide, the mechanical strength, wear resistance, and high-temperature resistance of the cemented carbide cutting tool material are enhanced.

[0055] In Comparative Example 5, the additive prepared without carboxymethyl cellulose aqueous solution was added to the cemented carbide cutting tool material, resulting in a decrease in its performance. This demonstrates that carboxymethyl cellulose decomposes upon heating to form carbon elements. These carbon elements can react with zirconium powder, tantalum powder, and molybdenum powder to form zirconium carbide, tantalum carbide, and molybdenum carbide, which fill the grain boundaries of the cemented carbide cutting tool material, increasing its density and thus improving its mechanical strength, wear resistance, and high-temperature resistance. Furthermore, the carbon elements provided by carboxymethyl cellulose can also participate in the reaction of titanium dioxide to form titanium carbide. The formed titanium carbide coats the surface of the composite carbon fiber, thereby fixing the metal carbides formed during the sintering process of the composite carbon fiber and preventing the metal carbides from easily slipping under high-temperature impact loads, which would affect the mechanical strength, wear resistance, and high-temperature resistance of the cemented carbide cutting tool material.

[0056] Comparative Example 6 showed that when additives prepared without titanium dioxide sol were added to cemented carbide cutting tool material, its performance decreased. This demonstrates that during the sintering process, titanium dioxide in the titanium dioxide sol can react with tungsten carbide to generate titanium carbide with high hardness. These titanium carbide particles are dispersed in the matrix and can jointly bear the applied load, thereby improving the mechanical strength, wear resistance, and high temperature resistance of the cemented carbide cutting tool material.

[0057] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0058] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

Claims

1. A high-strength, wear-resistant cemented carbide cutting tool material, characterized in that, The raw materials include the following parts by weight: 90-100 parts tungsten carbide powder, 13-15 parts cobalt powder, 3-5 parts nickel powder, 2-3 parts molybdenum powder, and 2-3 parts additives; The additive is obtained by reacting composite carbon fibers with tetrabutyl titanate. The composite carbon fiber is obtained by synthesizing a porous carbon layer on the surface of pretreated carbon fiber, and then mixing and reacting it with carboxymethyl cellulose, zirconium powder, tantalum powder and molybdenum powder.

2. The high-strength wear-resistant cemented carbide cutting tool material according to claim 1, characterized in that, The additive is prepared by the following steps: A1. Mix glucose, potassium hydroxide and deionized water, stir well to form a mixture, impregnate carbon fiber in the mixture, remove it after impregnation, dry it until the water evaporates, place it in a tube furnace, introduce nitrogen gas, carbonize at 750-850℃ for 3-4 hours, remove it, cool it to room temperature, wash it, dry it to obtain modified carbon fiber. A2. Mix zirconium powder, tantalum powder, molybdenum powder and carboxymethyl cellulose aqueous solution, stir evenly, then add modified carbon fiber, stir at 80-120 r / min for 20-30 min, let stand, filter, wash, and dry until the water evaporates to obtain composite carbon fiber; A3. Add tetrabutyl titanate to ethanol and deionized water, stir at 40-50℃ for 1-2 hours, cool to room temperature, add hydrochloric acid to adjust the pH to 2-3, and continue stirring to obtain titanium dioxide sol; mix titanium dioxide sol with composite carbon fiber and stir evenly to obtain additive.

3. The high-strength wear-resistant cemented carbide cutting tool material according to claim 2, characterized in that, In step A1, the mass ratio of glucose, potassium hydroxide and deionized water is (5.5-5.8):(4-4.5):

100.

4. The high-strength wear-resistant cemented carbide cutting tool material according to claim 2, characterized in that, In step A1, the mass ratio of the carbon fiber to the mixture is (20-25):

100.

5. The high-strength wear-resistant cemented carbide cutting tool material according to claim 2, characterized in that, In step A2, the mass ratio of zirconium powder, tantalum powder, molybdenum powder, carboxymethyl cellulose aqueous solution and modified carbon fiber is 1:1:1:(90-120):(5-5.5).

6. The high-strength wear-resistant cemented carbide cutting tool material according to claim 2, characterized in that, In step A3, the mass ratio of tetrabutyl titanate, ethanol and deionized water is (13-17):(30-40):(8-12).

7. The high-strength wear-resistant cemented carbide cutting tool material according to claim 2, characterized in that, In step A3, the mass ratio of the titanium dioxide sol to the composite carbon fiber is (0.2-0.4):

1.

8. A method for preparing a high-strength, wear-resistant cemented carbide cutting tool material as described in any one of claims 1-7, characterized in that, The preparation steps include the following: S1. Tungsten carbide, cobalt powder, nickel powder, molybdenum powder, and additives are mixed, vacuum dried, and ball-milled to obtain a mixture; S2. The mixture is placed in a pressure mold to be pressed into a preform, and then the preform is placed in a sintering furnace for sintering and solid solution strengthening. After cooling to room temperature, it is ground and sharpened to obtain cemented carbide cutting tool material.

9. The method for preparing a high-strength, wear-resistant cemented carbide cutting tool material according to claim 8, characterized in that, In step S1, the vacuum drying specifically involves a drying temperature of 70-90℃, a vacuum degree of 4-6Pa, and a drying time of 1-2 hours.

10. The method for preparing a high-strength, wear-resistant cemented carbide cutting tool material according to claim 8, characterized in that, In step S2, the sintering specifically involves heating to 1200-1400℃ at a rate of 2-5℃ / min and sintering for 2-3 hours.